Analysis of the Role of Stakeholders in Tourism Attraction Development Policy in Sumedang Regency - Ilhami, Rizky (Jurnal Pendidikan Indonesia, 2023)
This research aims to analyze the role of stakeholders in the formulation, implementation and evaluation of tourism development policies in Sumedang Regency. With the rapid growth of the tourism industry, it is important to understand how various stakeholders contribute to the development of tourist attractions in the area. This research uses a qualitative approach by collecting data through in-depth interviews, participant observation, and analysis of documents related to tourism policy. The research results show that coordination between stakeholders in developing tourism destinations in Sumedang Regency still needs to be improved, while the utilization of marketing potential through tourism websites is not yet optimal. Even though social media is widely used, the emphasis on the image of Sumedang Regency's leading tourist destinations in marketing strategies needs to be increased. Efforts to socialize the values of Sapta Pesona by Pokdarwis have proven effective in strengthening tourism awareness and creating a friendly and clean tourism environment, however, a stronger emphasis is still needed on this aspect in an effort to increase the attractiveness of tourist destinations.